Moderating effect of competitiveness on the relationship between ownership and segment disclosure: Evidence from Malaysia and selected developed Australasian Markets / Jalila Johari - Jalila , Johari (2015)
This study examines the relationship between firm ownership (managerial, family, institutional and foreign) and the extent of segment disclosures and whether firm and industry level competitiveness moderate this relationship in the emerging (Malaysia) and developed (Australia, Hong Kong and Singapore) markets. The findings confirm that in the Malaysian market managerial ownership is significantly and negatively associated with the extent of segment disclosure and the relationship is greater for firms with higher firm level competitiveness. Similarly, family and founding family ownership is significantly associated with the extent of segment disclosure but this association is greater for firms with higher firm and industry level competitiveness. Institutional and foreign ownership are not significant associated with the extent of segment disclosure in the emerging market, Malaysia. In contrast, in the developed markets, the effect of family and founding family and institutional ownership on the extent of segment disclosure is lesser for firms with higher firm level competitiveness, whilst the effect of managerial ownership on the extent of segment disclosure is greater for firms with higher industry level competitiveness only. Interestingly, in developed market the effect of foreign ownership on the extent of segment disclosure is greater for firms with higher firm level competitiveness. The findings reaffirm the role of competitiveness on segment disclosures and that ownership matters as the prior studies have shown inconclusive results on the association between ownership types and disclosures in general. In comparative between the emerging market and developed market, this study has proved that the negative relationship between the extent of segment disclosure and managerial ownership is stronger when firm level and industry level of competitiveness is high. Although agency theory suggests that managers have incentives to disclose financial information that are in favour to the user, the situation differs for segment information disclosures. Instead, in the presence of high firm level and industry level of competitiveness, firms with greater managerial ownership provide lower level segment disclosure in the emerging market as compared to the developed market. It is clear that in the emerging market, competitiveness at either firm level or industry level matters more for managerial ownership. As for institutional ownership, it is found that the firm level of competitiveness moderates the relationship between institutional ownership and the extent of segment disclosure. However, the moderating effect is stronger for firms that operate in lower firm level of competitiveness as compared to the higher firm level of competitiveness. The negative moderating effect is greater for institutional investors in the emerging market as compared to the developed market. The findings give further evidence that the firms with greater institutional investors in the emerging market have more incentivised to enhance the extent of segment disclosure particularly the firms with lower level of firm competitiveness as compared to the firms with higher level of competitiveness. Thus, the lower firm level of competitiveness does matter more for institutional ownership. This study provides useful insights for both policy makers and academic researchers to improve the extent of segment disclosure and eventually complement the level of transparency among firm in the emerging market with the developed market in order to accomplish the convergence towards the IFRS by the public listed firms all over the world.